Ecological and economic organization of crowning territory and arrangement of existing land in the Right-bank Forest-and-Steppe of Ukraine - Kyryliuk, V.; Borovyk, P.; Kyselov, Y.; Kyseliova, O. (Land Management, Cadastre and Land Monitoring, 2022)
The article analyzes the current land use of Dzendzelivske LLC of Mankivka village community of Uman district of Cherkasy region (former Dzendzelivska village council), which showed that the agro-ecological condition of agricultural lands before the project was in deteriorating condition and required sound land use solutions.The purpose of the work is to assess the ecological and economic justification of the organization of the territory of LLC "Dzendzelivske", ensuring the rational use and protection of land, creating a favorable ecological environment and improving agricultural landscapes. The proposed project solutions are based on the provisions of the regulatory framework and take into account environmental and economic requirements for the rational use of agricultural land. Based on the qualitative characteristics of agricultural groups of soils and their economic evaluation, the classes of suitability of arable lands for growing crops have been identified. Within the limits of the allocated classes of arable lands on ecological and economic suitability of soils for cultivation of agricultural crops introduction of soil protective (grassland) crop rotation is provided. During the implementation of ecological and economic land management of the territory, the natural resources of the allotted land plot should be mobilized, which will provide an opportunity to obtain quality plant products and at the same time preserve the natural environment and organize environmentally friendly production.Key words: ecological and economic substantiation, rational land use, technological groups of lands, organization of lands, crop rotations, transformation of lands, land management project, landscaping